Experimental Study of Energy Dissipation at Baffled Chute Spillway - Joko Nugroho; Indratmo Soekarno; Agung Wiyono Hadi Soeharno (Institut Teknologi Bandung, 2019)
Experimental observation on a model of free over flow spillway is used in this study. Three configurations of baffle placement are used in the experiment. The energy along the flow over the spillway were calculated based on measured flow depth and discharge during the experiment. Variations of flow depth and discharge were determined based on baffle height as a reference. The experiments were done in a 7 meters long flume of 0.078 m wide. The spillway model has a dimension of 17.2 cm high, with rounded crest and 1:1 downstream slope. There is no structures placed at the downstream of spillway. The discharge applied to the spillway model is in the range of 0.6 to 1.8 l/s. The experimental results shows that optimum results of energy dissipation were obtained when the flow depth is equal to the height of the baffle. Observed energy dissipations in this is in the range of 30% to 50% upon the incoming energy of the spilled flow. It was also observed that the length of the hydraulic jumped is reduced due to the application of baffled chute.Pengamatan eksperimental pada model pelimpah digunakan dalam penelitian ini. Tiga konfigurasi penempatan baffle digunakan dalam percobaan. Energi sepanjang aliran di atas spillway dihitung berdasarkan kedalaman aliran dan debit yang diukur selama percobaan. Variasi kedalaman aliran dan debit ditentukan berdasarkan tinggi baffle sebagai referensi. Percobaan dilakukan dalam flume 7 meter panjang lebar 0,078 m. Model spillway memiliki dimensi tinggi 17,2 cm, mercu bulat dan kemiringan hilir 1: 1. Tidak ada struktur yang ditempatkan di hilir spillway. Debit yang diterapkan pada model pelimpah berada dalam kisaran 0,6 hingga 1,8 l/s. Hasil eksperimen menunjukkan bahwa hasil optimal disipasi energi diperoleh ketika kedalaman aliran sama dengan ketinggian baffle. Disipasi energi yang diamati dalam penelitian ini adalah sekitar 30% sampai 50% pada energi yang masuk dari aliran yang melalui pelimpah. Dalam eksperimen diamati bahwa panjang loncatan hidrolik berkurang karena penerapan baffle pada saluran peluncur.